PENGARUH PENYULUHAN GIZI-KESEHATAN DAN FAKTOR LAINNYA TERHADAP PERTUMBUHAN ANAK USIA PRASEKOLAH - Yuliana Yuliana; Ali Khomsan; Soemiarti Patmonodewo; Hadi Riyadi; Deddy Muchtadi (Jurnal Gizi dan Pangan, 2006)
The objective of this study was to analyze the effect of extension on nutrition-health and other factors on the growth of pre-school children.  The design of this study was a quasi experiment. The subjects of this study were pre-school children aged 3-6 year old with  some specified criteria, such as having no story of severe malnutrition and low birth weight, having a complete parents, literacy ability of the mother, stated in a health condition/undefect handicapped, and did not follow any programs of early-age children education. The subjects were divided into two groups, namely group of control and group of intervention. The primary data collected consisted of family’s characteristics, child’s characteristics, and children’s care and development environment. Generally, there was no significant difference between pre- and post-test of mother’s knowledge on nutrition-health, both of control and intervention groups; however, there was a slightly difference on child-care on nutrition-health for the two groups. There was a significant difference on mother’s knowledge on nutrition-health between pre- and post- extension on the both groups.  About 51.3% of child’s growth was determined by factors of family and children.  The factors which had a possitive significant influence were body lenght, and mother’s knowledge on nutrition-health.